2015
DOI: 10.1111/nmo.12718
|View full text |Cite
|
Sign up to set email alerts
|

The relationship among gastroparetic symptoms, quality of life, and gastric emptying in patients referred for gastric emptying testing

Abstract: In patients referred for GET, gastroparetic symptoms were more severe in those with delayed emptying. A decrease in quality of life in those with delayed gastric emptying was also present; this was not related to the severity of the delay in gastric emptying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 28 publications
2
27
0
1
Order By: Relevance
“…Regarding the scintigraphic evaluation, the discordance rate was 21%, but in all the cases but one, the gap was in favour of a clinical improvement despite still disturbed GES. This could be explained by the sensibility of this examination, known to be imperfect, even if a disturbed GES is correlated with the severity of the disorder . Interestingly, all the discordances were observed in case of idiopathic gastroparesis.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the scintigraphic evaluation, the discordance rate was 21%, but in all the cases but one, the gap was in favour of a clinical improvement despite still disturbed GES. This could be explained by the sensibility of this examination, known to be imperfect, even if a disturbed GES is correlated with the severity of the disorder . Interestingly, all the discordances were observed in case of idiopathic gastroparesis.…”
Section: Discussionmentioning
confidence: 97%
“…Similar associations between vomiting, early satiety, and delayed gastric emptying were also observed in other gastric motility disorders, such as gastroparesis. DiBaise et al [18] demonstrated that severities of postprandial fullness/early satiety and nausea/ emesis, but not the bloating, in gastroparesis were correlated with severity of gastric emptying delay measured by scintigraphy. Furthermore, a prospective study by Ron et al [19] in 111 consecutive gastroparesis patients showed that only early satiety was associated with delayed gastric emptying measured by breath test.…”
Section: Discussionmentioning
confidence: 99%
“…The poor correlation between symptoms and objective measures of gastric emptying is well known. 6,27,28 Thus, the decision to offer the individual diabetes patient GES was based on a history of recurrent nausea and/or vomiting and not on a strict diagnosis of GP. GES is a relatively expensive procedure, mainly because of the price of the electrode and battery, which is approximately €13.000.…”
Section: Discussionmentioning
confidence: 99%
“…5 The majority of diabetes patients with delayed gastric emptying remain asymptomatic, and severe symptoms can be present even if gastric emptying tests are normal. 6 Thus, treatment is usually initiated based on recurrent episodes of nausea and/or vomiting rather than a diagnosis of GP based on gastric emptying tests. Dietary modifications are the first line of intervention for recurrent nausea and/or vomiting in diabetes patients.…”
Section: Introductionmentioning
confidence: 99%